PENGARUH BUDAYA ORGANISASI TERHADAP DISIPLIN DAN PRODUKTIVITAS WARTAWAN TRIBUN PEKANBARU - Ujang Jaya; Samsir '; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the influence of organizational culture on discipline Tribune reporter Pekanbaru, to analyze the influence of organizational culture on productivity Tribune reporter Pekanbaru, and to analyze the effect on productivity discipline Tribune reporter Pekanbaru. The population in this study are all Tribune reporter that the 36 journalists plus 25 freelance journalists. So the sample size determined as 61 respondents. Thus, the entire population sampled with a sampling technique census conducted. To perform data analysis, data processing is done using path analysis (path analysis) using PASW statistics 18.0 for windows. Discipline is positioned as a moderating variable that connects between the independent variables and the dependent variable. The method is an extension of path analysis used multiple linear regression to estimate the causal relationship between the bariabel in the research model that builds on a strong theoretical foundation. The results reveal that it can be seen that the influence of organizational culture on discipline peneiltian obtained results that the organizational culture does not significantly influence the discipline of journalists at the newspaper stands pekanbaru. Means Hypothesis 1 was rejected. The influence of organizational culture on productivity journalist obtained the results that organizational culture significantly influence productivity tribune newspaper reporter in Pekanbaru. Means Hypothesis 2 is accepted. Organizational culture should especially for journalists who always worked outside the office can create a high level of honesty that news provided better quality. Honesty in the sense of actually looking for news and all the news that is deemed worthy of publication, to be published. Do not be influenced by the material in the form of bribery that the news is not published. Reporter further enhanced productivity by providing education and training to journalists in the form of journalistic training, especially for new reporters for news and more news writing quality and socially acceptable.Keywords: Organizational Culture, Discipline and Productivity